Prionotropis xausi, a new species of Thrinchinae (Orthoptera: Pamphagidae) from Catalonia (northeast of the Iberian Peninsula) - Olmo-Vidal, Josep Maria (Zootaxa, 2020)
A new species of the genus Prionotropis Fieber, 1853 is described from Catalonia (Northeast of the Iberian Peninsula). Prionotropis xausi n. sp. was collected in a steppic calcareous grassland with low shrubs and scattered rocks, dominated by Buxus, Arctostaphylos uva-ursi, Thymus and Poa species. P. xausi n. sp. is characterized by the pronotum in dorsal view narrow and in lateral view with the principal transverse sulcus between prozona and metazona clearly incised. Females squamipterous with the tegmina extending at most to the end of second abdominal segment. Males sub-brachypterous with the tegmina reaching the 5th abdominal tergite and the epiproct visible. Inside hind femora at the base to the middle part and inside hind tibia red. Phallic complex with the epiphallus more long than wide with short posterior edge and the penis valves long. This new species is compared to the similar species P. rhodanica Uvarov, 1923 , P. azami Uvarov, 1923 and P. hystrix (Germar, 1817) and to the species presents in Catalonia P. flexuosa (Serville, 1838) and P. ancosae Olmo-Vidal, 2017. P. xausi is the species of the genus Prionotropis with the smallest males.